КѲЗ ҚАРАШЫҒЫ ЖӘРДЕМИНДЕ АУТЕНТИФИКАЦИЯЛАЎ УСЫЛЫ - Арзиева, Ж.Т.; Калмуратова, С.М.; Сейтниязов, Н.Б.; Жанхожаев, А.А. (FAN va JAMIYAT, 2021)
Today biometric systems are widely used in many fields. Algorithms for identifying factors that characterize the images of biometric objects based on the pupil of the eyes can improve the accuracy of personality recognition.